Monopoly, Quality, and Network Externalities - Luca Lambertini; Raimondello Orsini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1998)
We describe the behaviour of a monopolist supplying a vertically dierentiated good with network externalities. Assuming a fixed cost of quality improvements we show that the presence of network externalities enhances the incentive to expand output associated with scale economies. Although the quality distortion operated by the monopolist increases with network externalities, the outputexpansion effect is dominant, so that the welfare loss due to monopoly power shrinks as the role of network externalities in determining consumers' satisfaction becomes more relevant.
Keywords: 330